1993
DOI: 10.1113/jphysiol.1993.sp019895
|View full text |Cite
|
Sign up to set email alerts
|

Role of 5‐HT3 receptors in peristaltic reflex elicited by stroking the mucosa in the canine jejunum.

Abstract: SUMMARY1. The role played by the 5-HT3 receptor, a serotonin subtype receptor, in peristaltic reflexes was studied in dogs first given ketamine, then anaesthetized with urethane (10 g kg-', i.v.) and a-chloralose (100 mg kg-', i.v.). The jejunal loop was partitioned into two segments with respect to blood supply. Drugs were infused intra-arterially into each segment.2. Stroking of the mucosa of the aboral and oral segments elicited an ascending contraction and a descending relaxation, respectively.3. The ascen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…Mechanical stimulation of the mucosa is known to stimulate secretions via serotonin release 18 and to stimulate propulsive motility via 5-HT 3&4 receptor stimulation. 39 Nausea and stress induced by intubation also have a role in accelerating small bowel transit. 40,41 Stress from the intubation procedures or from disturbed sleep due to the presence of the tube might therefore have had an influence on the amount of SBWC.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanical stimulation of the mucosa is known to stimulate secretions via serotonin release 18 and to stimulate propulsive motility via 5-HT 3&4 receptor stimulation. 39 Nausea and stress induced by intubation also have a role in accelerating small bowel transit. 40,41 Stress from the intubation procedures or from disturbed sleep due to the presence of the tube might therefore have had an influence on the amount of SBWC.…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, it has been shown that stimulation of the 5-HT4 receptor increases longitudinal muscle contraction (Buchheit & circular muscle contraction during peristalsis in the guinea-pig isolated ileum Costall et al, 1993). The 5-HT3 receptor has also been shown to increase the ascending excitatory effect but not the descending inhibitory effect in the guinea-pig isolated ileum (Yuan et al, 1994), whereas Neya et al (1993) report that 5-HT3 receptor stimulation enhances both the ascending excitatory and descending inhibitory effects in the infused canine jejunum. Whilst the presence of the 5-HT3 receptor antagonist, tropisetron or ondansetron does not affect the threshold for peristalsis in the guinea-pig isolated ileum Costall et al, 1993), this does not exclude a 5-HT3 receptor involvement in the peristaltic reflex since a higher concentration of 5-HT has been shown to reduce the threshold for peristalsis by stimulation of a 5-HT3 receptor (Tuladhar et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…They rapidly depolarize neurons (20,47) by invoking a fast inward current (70,71), which is responsible for 5-HT-mediated fast neurotransmission (71). A combination of 5-HT 3 and 5-HT 4 antagonists inhibits the peristaltic reflex (39,51,52). 5-HT 3 antagonists decrease the frequency of migrating motor complexes in the isolated murine terminal ileum and colon (9).…”
Section: -Ht Is Utilized In the Bowel As A Neurotransmittermentioning
confidence: 99%